Rancang Bangun Purwarupa Alat Pembuka Pintu Garasi Menggunakan Limit Switch dan Fingerprint Berbasis Arduino - Juanda Manik; Joko Saputro; Yoga Listi Prambodo (FIKOM Universitas Bung Karno, 2023)
In everyday life, many activities are commonly performed manually. Therefore, it is not surprising that microcontroller-based technology is now being implemented, allowing manual processes to be automated. This research aims to address the dependency on human labor in manually opening and closing garage doors. A garage door is a mechanical device used to enclose the parking space for vehicles inside a house. The problem often faced by garage owners is the need for human assistance in opening the garage door. In this research, an innovative automatic device is proposed to open and close the garage door using a pressure sensor using limit switch and fingerprint sensor based on the Arduino microcontroller. By utilizing this technology, garage owners can easily operate the garage door without human intervention. The pressure sensor detects the position of the vehicle near the door, while the fingerprint sensor is used to provide restricted access only to authorized users.